The sociology of sport: Structural and cultural approaches - Young, T. R. (1986)
A Marxian theory of sport has two major dimensions: a political economy in which one weighs the degree to which sports serves the accumulation problems of advanced monopoly capital and a cultural-marxist dimension in which one examines the ways in which sports solves the problems of legitimacy and helps produce alienated consciousness in self and society. This paper provides insight in both uses to which commodity sports are put. In brief, advanced monopoly capitalism uses the advertising industry to olonize desire and myth in sports as an envelope in which to insert commercial messages. The human desire for good and enlivening social relations is transferred to the lifeless commodity. A better use of sports is to locate desire within community and interpersonal concerns rather than profit and a false solidarity. A radical research agenda is summarized in the last section.